PERANCANGAN SISTEM PENGENDALIAN MANAJEMENBERDASARKANBUSHIDO PADA DEPARTEMEN PPIC DI PT MASPION SIDOARJO - Yantrid Lisa Sabilla; Sujoko Efferin (Perpustakaan Universitas Surabaya, 2018)
Employees are the company's valuable asset. To keep the employees do well to carry out operational activities, a proper management control system is required. There are three types of complementary controls: result control, action control and cultural control. The purpose of this study is to explore and explain the relationship between the management control system with the application of Bushido values to overcome the deficiencies that occur in the department PPIC PT Maspion Sidoarjo. There are eight main values of Bushido used as a basis for overcoming the shortcomings. The research used is applied research with qualitative approach method. This research attempts to provide recommendations on the shortcomings contained in the PPIC department of PT Maspion Sidoarjo. The results of this study found that there are some deficiencies that occur in the operational activities of the department of PPIC due to lack of motivation in employees due to the weakness of the control system. The values in Bushido provide the basis for the researchers to provide recommendations to address the motivational problems that occur in employees.